3D-printed patient-specific instrumentation decreases the variability of patellar height in total knee arthroplasty - Wang, Junfeng; Wang, Xiaohua; Sun, Bin; Yuan, Liang; Zhang, Ke; Yang, Bin (Frontiers in Surgery, 2023)
Objective Three-dimensionally (3D) printed patient-specific instrumentation (PSI) might help in this regard with individual design and more accurate osteotomy, but whether the utility of such instrumentations minimizes the variability of patellar height in total knee arthroplasty (TKA) and the reasons for this effect are unknown. Our aim is to compare and analyze the variability of patellar height with PSI and conventional instrumentation (CI) in TKA. Methods Between March 2018 and November 2021, 215 patients with severe knee osteoarthritis who were treated with primary unilateral TKA were identified for this observational study. The patients were divided into the CI-TKA group and PSI-TKA group according to the osteotomy tools used in TKA. Preoperative and postoperative radiographic parameters including hip–knee–ankle angle (HKA), posterior tibial slope (PTS), Insall–Salvati ratio, modified Caton–Deschamps (mCD) ratio, anterior condylar offset (ACO), and posterior condylar offset (PCO) were evaluated. Results The groups were similar in patients' demographic data, clinical scores, and radiographic parameters preoperatively. Overall, according to the results of the Insall–Salvati ratio, postoperative patellar height reduction was noted in 140 patients (65.1%). Interestingly, the variability of patellar height was smaller in the PSI-TKA group. Radiographic evaluation revealed that the Insall–Salvati ratio after TKA had a minor change in the PSI-TKA group (p = 0.005). Similarly, the mCD ratio after TKA also had a minor change in the PSI-TKA group (p < 0.001). Compared to those in the CI-TKA group, the ACO (p < 0.001) and PCO (p = 0.011) after TKA had a minor change in the PSI-TKA group, but no minor PTS change (p = 0.951) was achieved in the PSI-TKA group after TKA. However, even with 3D-printed patient-specific instrumentation, there were still significant reductions in patellar height, ACO, PCO, and PTS after TKA (p < 0.001). Conclusion The variability of patellar height was sufficiently minimized with more accurate anterior and posterior femoral condyle osteotomy when 3D printed PSI was used. Furthermore, there was a trend in over-resection of the femoral anterior and posterior condyle and a marked reduction in PTS during TKA, which could lead to a change in patellar height and might result in more patellofemoral complications following TKA. Level of evidence Level II.